Towards Red Emissive Systems Based on Carbon Dots - Spyridon Gavalas; Antonios Kelarakis (Nanomaterials, 2021)
Carbon dots (C-dots) represent an emerging class of nontoxic nanoemitters that show excitation wavelength-dependent photoluminescence (PL) with high quantum yield (QY) and minimal photobleaching. The vast majority of studies focus on C-dots that exhibit the strongest PL emissions in the blue/green region of the spectrum, while longer wavelength emissions are ideal for applications such as bioimaging, photothermal and photodynamic therapy and light-emitting diodes. Effective strategies to modulate the PL emission of C-dot-based systems towards the red end of the spectrum rely on extensive conjugation of sp2 domains, heteroatom doping, solvatochromism, surface functionalization and passivation. Those approaches are systematically presented in this review, while emphasis is given on important applications of red-emissive suspensions, nanopowders and polymer nanocomposites.